The Effect of The Throat Length and The Hole Diameter in Throat Portion of The Venturi Nozzle on Aeration Efficiency - Koçyiğit, Şermin; Emıroglu, Muhammet Emin (My University, 2024)
Aeration is a procedure carried out to enhance water quality. Various hydraulic structures and devices for water aeration have been utilized in the literature. The venturi nozzle plays a significant role in water jet aeration. The aeration efficiency achieved with the venturi nozzle is seven times higher than that of the classic circular nozzle. In this experimental study, various holes of different sizes were created in the throat portion of the venturi nozzle; thus, air was drawn into the flow by creating negative pressure. The study examined the impact of the venturi nozzle on aeration efficiency by varying the length of the throat portion. The findings revealed that making a hole in the throat portion significantly improved aeration efficiency in-creasing the size of the throat portion had a detrimental effect.
Keywords: Aeration; Water jet; Oxygen transfer; Drinking and domestic water; Venturi nozzle.